Digital Health Promotion For Non-Communicable Disease Prevention Among Working-Age Adults: A Literature Review - Tukiman (STIKES Columbia Asia Medan, 2026)
Non-communicable diseases (NCDs) are the leading cause of global mortality, and behavioural risk factors including physical inactivity, unhealthy diet, tobacco use, and harmful alcohol consumption are highly prevalent among working-age adults. Digital health promotion has emerged as a scalable strategy to address these risks, but the evidence base is heterogeneous. This literature review aimed to synthesize evidence on digital health promotion strategies for the prevention of NCDs among working-age adults, including intervention approaches, behavioural and health outcomes, implementation characteristics, and research gaps. A structured search was conducted in PubMed, Scopus, Web of Science, and ScienceDirect, complemented by Google Scholar, focusing on peer-reviewed articles published between 2021 and 2026. Findings indicate that mobile health applications, wearable activity trackers, text-messaging platforms, social-media campaigns, and telehealth-supported programmes are the most frequently deployed modalities. Digital interventions produced small-to-moderate improvements in physical activity, dietary quality, weight, glycaemic control, and short-term smoking abstinence, particularly when they incorporated behaviour-change techniques such as goal setting, self-monitoring, feedback, and social support. Effectiveness was moderated by engagement, adherence, and digital health literacy, while sustainability and equity remained key concerns. Digital health promotion offers a promising complement to conventional strategies for NCD prevention among working-age adults, and future research should prioritize long-term outcomes, equity, and integration into workplace and primary-care settings.